Blood Urea Nitrogen-Serum Albumin Ratio As a Predictor of Clinical Outcome in Acute Ischemic Stroke - Suseno, Endy; Akbar, Muhammad; Bintang, Andi Kurnia; Soraya, Gita Vita; Lotisna, Mimi; Sompa, Andi Weri (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Stroke is a global health issue with high morbidity and fatality rates. Treatment decisions for ischemic stroke rely on clinical outcome prediction. The NIHSS score is commonly used to predict the AIS's clinical outcomes. However, its use is hindered by its complexity, which requires the assessment of many variables. Therefore, there is an urgent need to develop a simpler yet still effective evaluation tool in assessing the AIS’s clinical outcome. The study aimed to predict AIS outcomes using the blood urea nitrogen to albumin serum ratio (RBA). This study was a prospective cohort study design, with subjects being first-time AIS patients hospitalized at RSUP Dr. Wahidin Sudirohusodo and several hospitals in Makassar from December 2022–April 2023. Demographic and clinical data were collected, assessing RBA and comparing it according to the good (mRS 0-2) and poor (mRS 3-6) outcome groups. RBA performance was assessed by receiver operating characteristic curve (ROC) analysis to assess the AIS's clinical outcome. The study's findings on 62 participants meeting the criteria revealed a significant association between RBA and the AIS's clinical outcome (p-value=0,0004). The mean RBA differed significantly between the good and poor AIS outcome groups (p-value =0,006). In the ROC analysis, the area under the curve (AUC) was 0,75 with an optimal cut-off value was 2,05, yielding a sensitivity of 41,67%, a specificity of 98%, and a likelihood ratio of 20,83 (p-value=0,007). In conclusion, RBA can be used as a simple and objective tool to determine the clinical outcome predictors of AIS.